Effect of Pb2+ Ions on Photoluminescence of ZnS‐Coated AgInS2 Nanocrystals. Issue 3 (6th December 2017) - Podgurska, Iryna; Rachkov, Alexandre; Borkovska, Lyudmyla
Abstract : The effect of quenching of photoluminescence (PL) intensity of thiol‐stabilized water‐soluble ZnS‐coated AgInS2 nanocrystals (NCs) in the presence of Pb 2+ ions is investigated. The factors influencing the efficiency of quenching process such as NCs dilution, pH value, composition, and concentration of working buffer solution are studied. It is found that the increasing of NCs dilution as well as the acidity of buffer solution promotes PL quenching by Pb 2+ ions. In all media used, the decrease of PL intensity in the presence of Pb 2+ ions is accompanied by a red shift of the PL band. In 0.5 × 10 –3 m citrate buffer solution, the red shift reached almost 5 nm. The degradation of the PL intensity is attributed to formation of some substances at the NC surface acting as the centers of nonradiative recombination. The red shift is ascribed to different quenching effect of Pb 2+ ions on the PL intensity of NCs of different sizes. The bimodal distribution of the NCs is proved by the PL study of NC fractions separated by ultracentrifugation. The obtained results could be useful for development of novel methods for detection of heavy metal ions. Abstract : The decrease of photoluminescence intensity of thiol‐stabilized AgInS2 /ZnS nanocrystals in buffer solution after adding of Pb 2+ ions is studied. The effect is attributed to formation of nonradiative centers at the surface of nanocrystals and is larger for the nanocrystals of smaller size. The bimodal size distribution of nanocrystals is responsible for a red shift of the photoluminescence band.